Assessment of CRB1-Associated Retinopathies Using the S-MAIA Fast Protocol and Spectral-Domain Optical Coherence Tomography - Bethany E. Higgins; Ana Catalina Rodriguez-Martinez; Giovanni Montesano; Vijay K. Tailor-Hamblin; Samantha Malka; Robert H. Henderson; Mariya Moosajee (Biomedicines)
Background: A cross-sectional study was conducted at Moorfields Eye Hospital, UK, involving patients with CRB1-associated retinopathies: macular dystrophy (MD), cone-rod dystrophy (CORD), and early-onset severe retinal dystrophy/Leber congenital amaurosis (EOSRD/LCA). The study aimed to evaluate CRB1-associated retinopathies using microperimetry (macular integrity assessment (S-MAIA) fast protocol) and spectral domain optical coherence tomography (SD-OCT). Methods: Data quality and participant attrition were assessed in 18 patients (10 MD, 5 EOSRD/LCA, 3 CORD), aged 10–52 years, with a median best corrected visual acuity (BCVA) of 0.41 logMAR. Results: Microperimetry and SD-OCT data were obtained from 14 and 18 patients, respectively, but eccentric fixation hindered structure-function analysis. All participants showed overall abnormal sensitivity on the S-MAIA fast protocol. Parafoveal volume was significantly increased, while foveal thickness and volume were reduced compared to normative data (p < 0.01). Conclusions: This study highlights the challenges of participant attrition and the need for alternative functional metrics to complement traditional evaluations. It also reinforces previous findings of abnormal retinal architecture in CRB1-associated retinopathies, providing further insights into S-MAIA and SD-OCT assessments for this patient population.